FACTORS AFFECTING STUDENTS’ LOW MOTIVATION IN LEARNING ENGLISH AT SMK MAMBAUL ULUM JAMBI - Putri Rodiyanti (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2023)
This study is purposed to find out factor of affecting students’ low motivation in learning English at high school. This study used qualitative case study as the design. To collect the data, the researcher conducted interviews and observations with respondents to find out the problems students’ low motivation in learning English..The interview consisted of 12 questions arranged according to the indicator by Gardner and Dornyei. Researchers used data analysis to identify students’ low motivation in learning English. The result of this study is the students eleventh grade of SMK Mambaul Ulum Jambi are low motivation in learning English. Then, the factors that affected are: internal factors (students self/individual, students’ interest, curiosity) and external factors (family factors, teacher factors, and environment factors). Suggestions for future researchers, it is hoped that this study will serve as a reference for researchers who low the motivation to investigate the same topic and that subsequent researchers will be able to learn more about it.